GENERAL INTERFACE BOX OF INDUSTRY CONTROL OF COMPUTER - MO HU (1991)
The utility model relates to a general interface box of industry control of computer which is used inside a sealed shielding box made of metal. The general interface box of industry control of computer is provided with a combined type switch voltage stabilizing power source, an interface for inserting a plurality of adaptation modules used for signal transformation and processing, and an input socket and an output socket of sampled signals; each component is interconnected by a parallel cable. The general interface box of industry control of computer can introduce a computer procedure control technique without too big alteration of the conventional equipment on industry site so as to realize the primary goal of electromechanical integration, and can make full use of high-tech products in the market; the utility model has the advantages of high reliability, mature technique, high performance-cost ratio, high versatility and wide application range.